Heterogeneous expectations, housing bubbles and tax policy - Carolin Martin; Noemi Schmitt; Frank H. Westerhoff (Bamberg University, Bamberg Economic Research Group (BERG), 2020)
We integrate a plausible expectation formation and learning scheme of boundedly rational investors into a standard user cost housing market model, involving a rental and a housing capital market. In particular, investors switch between heterogeneous expectation rules according to an evolutionary fitness measure, given by the rules' past profitability. We analytically show that our housing market model may produce endogenous boom-bust dynamics. Furthermore, we demonstrate that policy makers may use our model as a tool to explore how different tax policies may affect the housing market's steady state, its stability and out-of-equilibrium behavior.
Keywords: D84; H24; R31; 330; housing markets; bubbles and crashes; heterogeneous expectations; bounded rationality and learning; tax policy; steady state and stability analysis